The economics of discrimination: evidence from basketball - Lawrence M. Kahn (Institute for the Study of Labor (IZA), 2009)
This Chapter reviews evidence on discrimination in basketball, primarily examining studies on race but with some discussion of gender as well. I focus on discrimination in pay, hiring, and retention against black NBA players and coaches and pay disparities by gender among college coaches. There was much evidence for each of these forms of discrimination against black NBA players in the 1980s. However, there appears to be less evidence of racial compensation, hiring and retention discrimination against black players in the 1990s and early 2000s than the 1980s. This apparent decline is consistent with research on customer discrimination in the NBA: in the 1980s, there was abundant evidence of fan preference for white players; however, since the 1980s, these preferences seem much weaker. There appears to be little evidence of pay, hiring or retention discrimination against black NBA coaches, and while male college basketball coaches outearn females, this gap is accounted for by differences in revenues and coaches' work histories. There is some dispute over whether these revenue differences are themselves the result of employer discrimination.
urn:nbn:de:101:1-20090216118
Keywords: J71; L83; 330; Discrimination; race; gender; basketball; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Geschlechterdiskriminierung; Professioneller Sport; Ballsport; Sportler; USA